Diseminasi Pola Pengelolaan Keuangan Rumah Tangga: Perencanaan Biaya Pendidikan - Farida Komalasari; Eko Ganiarto (ACADEMICS IN ACTION Journal of Community Empowerment, 2019)
How low the financial literacy of many housewives as the ones who are in charge of the family’s finance in Indonesia causes many families who do not have an educational financial planning. This causes how common it is for some people who could not go to school because of their family’s financial problem. The purpose of this program is to show how it is to maintain the family’s financial status, to increase the awareness of how important educational financial planning is and to show how to plan their children educational finance. This program was held on Sunday, Dec 2nd at 4.05-6.00 pm and was participated by 24 community members. The visit was done by giving lecture, quiz, question & answer, and discussion. The participants were really enthusiastic and active through the whole activity and wanting to attend the same activity with a different topic. An activity with different topic can be held with either the same or different community. The topics they suggested were how to save money, how to choose an insurance company, how to choose something to invest and how to raise children in a digital era.